Influence of Halal, Tayyib, Hygienic Food on Food Purchases in Bansari, Temanggung - Hidayat, Farid (Journal of Islamic Economy and Community Engagement, 2025)
The purpose of this study is to determine the influence of halal knowledge, halal awareness, tayyib, and hygiene on purchase intention, as well as purchase intention on purchase decision in Bansari District, Temanggung, Central Java. This study is quantitative research with a sampling method using simple random sampling, which was obtained by 125 respondents. The results of the study show that halal knowledge does not affect purchase intention. Meanwhile, halal awareness, tayyib, and hygiene have a significant positive effect on purchase intention, purchase intention has a significant positive effect on purchase decision. The path coefficient value of the halal knowledge variable to purchase intention was 0.491, the halal awareness variable to purchase intention was 0.000, the tayyib variable to purchase intention was 0.036, the hygienic variable to purchase intention was 0.000, and the variable was Purchase intention to a purchase decision of 0.000